2019
DOI: 10.1556/1848.2019.0001
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of various experimental wall fragments exposed to real climate conditions – temperature measurement

Abstract: Main aim of this paper is to illustrate the experimental partial results of a study on various exterior wall fragments. The study was performed for selected wall fragments and time periods, with attention focused also on wall orientation (East and South) with identical layering and also on dynamic thermal parameters connected to the thermal comfort during summer and winter. Evaluation is done for real measured climate conditions in the area of experimental laboratory (exterior – University of Zilina) and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…1 and 3). Detailed description of the wall sections and research outcomes can be found in [11,12]. Composition of section with ventilated cladding (Fig.…”
Section: Wall Compositionmentioning
confidence: 99%
“…1 and 3). Detailed description of the wall sections and research outcomes can be found in [11,12]. Composition of section with ventilated cladding (Fig.…”
Section: Wall Compositionmentioning
confidence: 99%